An epidemiological study of hepatitis virus infection in psychiatric patients in East China - Taixiu Liu; Ruirui Chen; Deyun Bu; Zheng Shi; Heng Zhang; Wu Li; Dong Liu (BMC Public Health)
Abstract Backgrounds Psychiatric patients have been the focus of social attention, and they may be more susceptible to hepatitis viruses. This study aims to investigate the prevalence and influencing factors of hepatitis virus infection among psychiatric patients in East China. Methods A total of 6,5911 newly admitted psychiatric patients at Shandong Daizhuang Hospital from 2017 to 2023 were included in this study. Test results of serum biomarkers for HBV and HCV infection were collected from psychiatric patients. Background information such as sex, age, ethnicity, marital status, occupation, residence, region, and types of psychosis were collected. Results of serum markers for hepatitis B and C were also collected from 23,628 non-psychiatric individuals. Results In the study area, the HBV infection rate in psychiatric patients was 3.75% (95% CI: 3.46–3.74%) and showed a decreasing trend by year (p for trend = 0.000). The HCV infection rate in psychiatric patients was 0.23% (95% CI: 0.19–0.27%). The HBV infection rates differed among sex, age, marital status, occupation, residence, region, severity, and psychosis types. The HCV infection rates differed among age, marital status, occupation, and psychosis types. The HBV infection rate in psychiatric patients was positively skewed with age, being lowest in the age group of 5–15 years old and the highest in the age group of 36–40 years old, similar to the distribution of HBV infection in non-psychiatric patients. The HCV infection rate in psychiatric patients increased with age (p for trend = 0.000) and was similar to non-psychiatric patients (p for trend = 0.000). Compared with non-psychiatric patients, the “Mental and behavioural disorders due to use of alcohol”, “Schizophrenia”, “Mental disorders due to epilepsy”, “Behavioural and emotional disorders with onset usually occurring in childhood and adolescence”, “Obsessive-compulsive disorder”, “Somatoform disorders” and “Depressive episode” become influencing factors for HBV infection. Compared with non-psychiatric patients, the “Dementia in other diseases classified elsewhere”, “Depressive episode” become influencing factors for HCV infection. Being male, jobless and living in rural were risk factors for HBV infection, and urban became a risk factor for HCV infection. Discussion and conclusion The rate of HBV and HCV infection among psychiatric patients in this region have remained low. Gender, age, occupation, residence, and types of psychosis were identified as potential influencing factors for hepatitis virus infection.